Pedestrian caution:: hybrid creation processes - Birck, Marcelo de Campos Velho (Farol, 2024)
The article is a video that addresses user/technology relationships, through animations, archive scenes, performances and reused materials. To this end, I establish analogies between visual arts, cinema and music. I highlight the coexistence of assembly and journey in cubist, Dada and Pop Art works. As a complement, I use Visual Music. Method: DIY. Reference authors: Peter Vergo, Vincent Amiel, Nicolas Borriaud, Marshall McLuhan and Barrington Nevitt, Edmond Couchot and Thomas Levin.